2015
DOI: 10.1016/j.desal.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

The anti-biofouling properties of thin-film composite nanofiltration membranes grafted with biogenic silver nanoparticles

Abstract: 2015) 'The anti-biofouling properties of thin-lm composite nanoltration membranes grafted with biogenic silver nanoparticles. ', Desalination., Further information on publisher's website: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 39 publications
(31 reference statements)
2
41
0
Order By: Relevance
“…It is well known that Donnan exclusion and steric repulsion mechanism are the two critical factors for the studied polyamide NF membrane [51,52]. A strong electrostatic repulsion between the multivalent anions (SO 4 2− ) and the polyamide layer surface will result in a higher rejection of multivalent anions (SO 4 2− ) than that of monovalentions (Cl − ). The hydrophilic membranes modified by the addition of a small amount of ZnO nanospheres could maintain a good salt separation capability and a high water flux.…”
Section: Separation Performance Of the Hfc Nanofiltration Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that Donnan exclusion and steric repulsion mechanism are the two critical factors for the studied polyamide NF membrane [51,52]. A strong electrostatic repulsion between the multivalent anions (SO 4 2− ) and the polyamide layer surface will result in a higher rejection of multivalent anions (SO 4 2− ) than that of monovalentions (Cl − ). The hydrophilic membranes modified by the addition of a small amount of ZnO nanospheres could maintain a good salt separation capability and a high water flux.…”
Section: Separation Performance Of the Hfc Nanofiltration Membranesmentioning
confidence: 99%
“…Most of NF membranes are thin-film composite (TFC) membranes with the active layer commonly formed on the top surface of porous flat sheet membranes [4,5]. With the self-support structure and high-packing density, hollow fiber membrane used as the support for the preparation of composite NF membrane has attracted more and more attention [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Unfortunately, as with all of the membrane ltration processes, an inherent problem with NF is the reduced production efficiency due to fouling of the membrane surface by microorganisms, colloidal materials and dissolved organics. [5][6][7] The main factors affecting membrane fouling are roughness and hydrophilicity, as well as the chemical and physical properties of the feed water. 8,9 The fouling extent of the membrane varies, depending on the structural properties of the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there are also various membranes reported by loading silver (silver ion or nanoparticle) onto the membrane surface through different methods to improve the anti-biofouling performance. [67][68][69][70][71][72][73][74][75][76] For example, Dong et al in situ immobilized silver nanoparticles (AgNPs) onto the commercial polyamide RO membrane (virgin membrane) surface via a two-step surface modication process to improve the membrane's anti-biofouling property. 68 Chou et al prepared the silver-loaded cellulose acetate hollow ber membrane by dissolving AgNO 3 in the polymeric casting solution, and the hybrid membrane was evaluated antibacterial activity against both Escherichia coli and Staphylococcus aureus.…”
Section: Introductionmentioning
confidence: 99%
“…70 Liu et al also demonstrated that the hybrid PA/Ag nanocomposite membrane possessed dramatic anti-biofouling effect by using layer-by-layer (LbL) assembly method. 73,74 Wu and Yang et al loaded Ag nanoparticles by using polydopamine (PDA) as nano-template on the PA layer and the resultant nanocomposite membranes showed the potential towards long lasting and regenerable anti-biofouling ability in membrane systems. 75,76 Obviously, loading silver onto the polymeric membrane makes signicant contribution to membrane anti-biofouling performance.…”
Section: Introductionmentioning
confidence: 99%